Cloud Point Extraction Coupled to Flame Atomic Absorbance Spectroscopy for Cobalt (II) determination with Azo-Azomethine Dye - Affat, Sajda; Al – Shamkhawy, Saher; Snigur, Denys (University of Thi-Qar Journal of Science, 2024)
The azo-azomethine dye 6,6'-((1E,1'E)-((4-methyl-1,2-phenylene)bis(azanylylidene))bismethanylylidene))bis(2-methoxy-3-(o-tolyldiazenyl) phenol) (L3) were synthesized and characterized by UV-visible, FT-IR, 1H-NMR and Mass spectroscopy. The effect of the several factors on the CPE pre-concentration of Cobalt (II) with L3 was optimized. Extensive thermodynamic study has been presented to understand the mechanism of extraction and solubilization of studied complex in Triton X-100 micelles. Under the optimized conditions, enrichment factor of 54 is achieved leading to limit of detection and limit of quantitation of 11.5 and 38.4 ngmL-1 respectively. Under the optimal conditions the calibration plot is linear in the range of 0.025-3 μg mL-1, the precision (RSD%; n=8) of the proposed method is of 0.823% at 0.05 μg mL-1 of Co (II). This method is applied to the determination of Co (II) in various environmental samples.